Novel DNA-based electronic profiling method for selected algae / Siti Zulfikriyah Azmi - Siti Zulfikriyah , Azmi (2019)
The utilization of deoxyribonucleic acid (DNA) in electronics has become significant and gradually accepted by researchers due to its remarkable characteristics. There are several devices and sensors that employ DNA in their fabrication process. The standard methods to detect and recognize any species of living organism are polymerase chain reaction (PCR), sequencing and microarray techniques. However, there are several drawbacks pertaining to these methods such as sample contamination, misleading results as well as being costly and involving complicated procedures. As an alternative method, this study presents a simple, fast, high sensitivity and economical novel identification method for algae-derived DNA using the electronic properties of DNA. Novel current-voltage (I-V) characteristics of chosen algal species using DNA-specific diodes were obtained and its corresponding diode parameters (turn-on voltage, shunt and series resistance, knee voltage, breakdown voltage as well as breakdown current) were then calculated in this study. Each algal species exhibits specific turn-on voltage values for example Chlorella sp. had a value of 1.40 V, Synechococcus sp. with 1.15 V and Amphora sp. with 1.36 V. This novel technique demonstrates an exciting potential that may have huge impact in various fields, especially in pathology and taxonomy.